From the Ground Up : Perspectives on Post-Tsunami and Post-Conflict Aceh - Daly, Patrick T., 1975-; Feener, R. Michael; Reid, Anthony, 1939- (Book collections on Project MUSE., 2012)
The tsunami that struck a dozen countries around the Indian Ocean on 26 December 2004 evoked international sympathy on a scale beyond any previous natural disaster. The international relief effort broke all records both in scale and diversity, with seven billion U.S. dollars donated from all over the world through public and private agencies for Sumatra alone. Simply as a reconstruction effort, therefore, the disbursement of those funds and the rebuilding of housing, infrastructure, and economy posed major national and international challenges. However this was not simply a reconstruction effo.